KAJIAN PENGEMBANGAN PARIWISATA TANJUNG LESUNG BANTEN UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT Study of Tanjung Lesung Tourism Development to Improvethe Society Welfare - Wawanudin, Wawanudin; Juanda, Bambang; Fauzi, Ahmad (Jurnal Manajemen, 2018)
This paper study on the Tourism development of Tanjung Lesung Banten in order to improve the welfare of the community. This study aimed to 1) to analyze existing condition of Tanjung Lesung tourism, 2) to analyze the role of Tanjung Lesung tourism towards the improvement of society welfare 3) to analyze factors that influence income of local peoples in Tanjung Lesung 4) to set alternative idea of Tanjung Lesung tourism development that can improve people's welfare. The research method used mix method, which combines quantitative and qualitative research. Data analysis includes; descriptive analysis, exact test fisher analysis, test U mann withney analysis, and multiple regression analysis. Results of this study indicate that the absorption of commodities from the local area is still very small, whether from kinds of the commodity and its quantity. From total commodities transactions, 62.4% was spent in Jakarta, only 14.8% in Labuan District, and 11.5% in Tangerang. These tourism activities have low effect on the local community economic, while the remote area receives more economic benefit than the local area. Tourism activity has not been proved has significant influence on increasing local community welfare. Factors that increase household income per capita are controlled by the number of the family member and the existence of side jobs. Local government, through the Village Owned Enterprises, needs to encourage cooperation with the management of Tanjung Lesung to use local commodities for their the supply Target investment plan of Pandeglang Regency and Central Government related to KEK Tanjung Lesung need to be followed up by Infrastructure needs to facilitate tourist access.Keywords: Tourism, Tanjung Lesung, KEK, Commodity, income, Welfare.